PENGARUH MEDIA KOMIK TERHADAP PENGETAHUAN DAN SIKAP PEMILIHAN MAKANAN JAJANAN PADA ANAK SEKOLAH DASAR ISLAM SWASTA AS SHOLIHAH KOTA MEDAN - Emi Inayah Sari Siregar; Abdul Hairuddin Angkat (Poltekkes Kemenkes Medan, 2023)
Introduction : Snacks have a role in providing energy and other nutritional intake for school-aged children. Snacks can contribute energy and other nutrients that are useful for children's growth. Children's knowledge and attitudes about choosing snacks are very important so that the snacks they choose are healthy snacks. Objective: to determine the influence of comic media on knowledge and attitudes towards choosing snacks among As Sholihah Primary School students. Design : quasi experimental, namely pre-test and post-test with control group design. The sample was four class student who were divided into 2 groups, each group consisting of 30 people, divided into groups with comic intervention and groups without treatment. Data analysis used the independent t-test to assess each variable, namely knowledge and attitudes towards choosing snack foods. Results : A significant difference was found in the average knowledge between the treatment group and the control group, with p-value = 0,012 < 0,05. Meanwhile, in the statistical test on the attitude category, the value obtained was p = 0,000 < 0,05. This means that there is a difference in the average score of students' attitudes regarding the choice of snacks between the treatment group and the control group. Conclusion : Counseling using comic media has an effect on increasing the knowledge and attitudes of As Sholihah Primary School students.